Resolution of halitosis following repair of a primary parahiatal diaphragmatic hernia - Sellars, James N.; Green, Ryan; Jeyarajan, Eshwarshanker (International Surgery Journal, 2024)
Parahiatal diaphragmatic hernias are uncommon and often diagnosed incidentally on imaging, or in the emergency setting. Symptoms related to these defects can be like those of hiatus hernias (HH), however this is not always the case. We present a unique case of parahiatal diaphragmatic hernia that was characterised by severe halitosis which resolved with surgical repair.